Hand–mobile phone culture-burden associations and taxon-level concordance among healthcare-associated personnel: a paired cross-sectional study - Wenjing Jiang; Chunli Song; Li Cao; Yuhan Zhang; Xiaoyu Liao; Yu Chen; Xianyu You; Suchuan Zhang; Juan Tang (Frontiers in Cellular and Infection Microbiology, 2026)
Background Hands and mobile phones are frequently handled during healthcare delivery and caregiving, but their participant-level culture-burden association and taxonomic overlap remain incompletely characterized. We examined whether paired hand and mobile-phone contamination was associated within individuals and whether the two sites showed overlap or discordant detection among culture-defined taxa. Methods We conducted a paired cross-sectional study in a tertiary Grade A general hospital between April and June 2026. Physicians, nurses, and professional caregivers each provided one hand sample and one paired mobile-phone sample. Because hand and mobile-phone burdens were expressed in different site-specific units, absolute burdens were not directly compared. Spearman rank correlation was the primary association analysis; separately standardized log-burden regression models were used for covariate adjustment. Binary culture-defined taxon profiles were evaluated using overlap metrics, exploratory paired-label multivariate analyses, and exact McNemar tests. Results A total of 126 participants were included. The median culture burden was 11.67 CFU/cm² (IQR, 1.67–54.17) for hands and 950.00 CFU/phone (IQR, 300.00–2575.00) for mobile phones. The site-specific burdens were positively associated (Spearman rho=0.514, P<0.001). After separate standardization of log10(CFU + 1) values within each site, the association remained in the core adjusted model (standardized beta=0.512, 95% CI 0.291–0.732; P<0.001) and the extended sensitivity model (standardized beta=0.497, 95% CI 0.276–0.718; P<0.001). Median Jaccard similarity was 0.50 among 119 pairs with at least one detected non-Other taxon, and the median shared-taxon count was 1 across all 126 pairs. Exploratory multivariate findings were sensitive to the analysis set and were not reproduced when restricted to pairs with non-Other taxa detected at both sites. Coagulase-negative staphylococci were the only prespecified taxon with significant discordant detection after multiplicity correction. Conclusions Paired hand and mobile-phone culture burdens showed a positive participant-level association and partial culture-defined taxonomic overlap. The cross-sectional culture-based design does not establish direct microbial transmission or causality. Prospective studies should evaluate whether coordinated hand-hygiene and device-cleaning approaches improve microbiological outcomes.